Karakteristik Tumbuh dan Hasil Empat Varietas Kedelai pada Berbagai Dosis Bokhasi pada Tanah Gambut Pedalaman - Erina Riak Asie (Fakultas Pertanian, Universitas Syiah Kuala, 2007)
Growth Characteristic and Yield of Four Varieties of Soybean Under Different Dosage of Bokhasi in Inland Peat SoilABSTRACT. The purpose of this research was to study the effect of various rate of bokhasi on growth characteristic and yield of four varieties of soybean in inland peat soil. Experiment was carried out at Agriculture Faculty Experiment Station of Palangkaraya University, from Mei to September 2005, Experiment used was randomized completely design of factorial pattern with two factors, that is: variety (Wilis, Baluran, Anjasmoro, and Sibayak); bokhasi (0, 5, 10, 15, and 20 ton ha-1). Result of the experiment showed that Anjasmoro variety more adaptive in inland peat soil and gave the good responses to bokhasi than Wilis, Baluran, and Sibayak. Net Assimilation Rate (NAR), Relative Growth Rate (RGR) increased as affected by bokhasi until 15 ton ha-1. On the other hand, application of 15 and 20 ton ha-1 bokhasi gave highest yield, that is 4,87-5,13 g per plant.